История СССР. 10 класс: учебник для средней школы / Ю. И. Кораблев, И. А. Федосов, Ю. С. Борисов - Кораблев Юрий Иванович (Просвещение, 1990)
Экземпляры: БС (20170802) / Инвентарный номер: РТШ48214 / Сис.шифр: 63.3(2)7 / Авт.знак: К 66 / ГРНТИ: 03.23 / ББК: 63.3(2)я7